KETERKAITAN KONSUMSI PRODUK BERLABEL HALAL DENGAN KETAATAN BERAGAMA - Hatoli Hatoli (Fakultas Syariah (Syari'ah Faculty ), 2020)
Halal products are a moral and material necessity. For Muslims, morally the product does not violate the rules of halal and haram in carrying out religious orders. Materially, this halal product is universal not only for Muslim societies, but also for all societies regardless of differences given that halal products aim to provide comfort, safety and legal certainty in consuming them. The Indonesian Ulema Council (MUI) is the agency authorized to research and provide fatwa on the halal illegality of a product so that it makes consumers feel safe and comfortable using the product without worrying about fulfilling their religious orders. Then what about products without the halal label, given the halal certification that is voluntary. Are Muslim consumers who consume these products included in the category of disobeying religious orders? And what is the position of this in view of Islamic teachings and law that they believe in? This paper would like to describe the correlation of halal labeled products with one's obedience in religion using qualitative research methods that are descriptive in nature, and the type of approach used is the empirical sociological legal approach, which is guided by regulations, books or legal literature and materials that have a relationship with the problem and discussion in this paper. Halal certification of a product issued by MUI does not mean forbidding other products without a halal label but aims to provide legal certainty and quality of a product and provide various benefits that can be obtained if the manufacturer provides halal guarantees on its products. But there is a more explicit need behind it, namely the spiritual need that is trying to be lived in, namely obedience in fulfilling religious orders.